Evaluation of Pochonia chlamydosporia and Purpureocillium lilacinum for Suppression of Meloidogyne enterolobii on Tomato and Banana - Silva, Silas D (Journal of nematology, 2017)
Meloidogyne enterolobii is one of the most important root-knot nematode in tropical regions, due to its ability to overcome resistance mechanisms of a number of host plants. The lack of new and safe active ingredients against this nematode has restricted control alternatives for growers. Egg-parasitic fungi have been considered as potential candidates for the development of bionematicides. In tissue culture plates, Pochonia chlamydosporia (var. catenulata and chlamydosporia) and Purpureocillium lilacinum strains were screened for their ability to infect eggs of the root-knot nematode M. enterolobii on water-agar surfaces. Reduction in the hatching of J2 varied from 13% to 84%, depending on strain. The more efficacious strains reduced hatchability of J2 by 57% to 84% when compared to untreated eggs, but average reductions were only 37% to 55% when the same strains were applied to egg masses. Combinations of fungal isolates (one of each species) did not increase the control efficacy in vitro. In experiments in which 10,000 nematode eggs were inoculated per plant, reductions in the number of eggs after 12 months were seen in three of four treatments in banana plants, reaching 34% for P. chlamydosporia var. catenulata. No significant reductions were seen in tomato plants after 3 mon. In another experiment with tomato plants using either P. chlamydosporia var. catenulata or P. lilacinum, the number of eggs was reduced by 34% and 44%, respectively, when initial infestation level was low (500 nematode eggs per plant), but tested strains were not effective under a moderate infestation level (5,000 eggs per plant). Under all infestation levels tested in this work, gall and egg mass indexes (MI) did not differ from the untreated controls, bringing concerns related to the practical adoption of this control strategy by farmers. In our opinion, if the fungi P. chlamydosporia and P. lilacinum are to be used as biocontrol tools toward M. entorolobii, they should focus on agricultural settings with low soil infestation levels and within an IPM approach